The relationship between company performance and CEO compensation for JSE versus ALTX listed companies in South Africa - Hurry, Robert James (My University, 2015)
An examination of companies listed on the JSE main board and Alternate Exchange in South Africa over a five year sample period provides evidence that, after controlling for company size, performance, growth opportunities and industry, CEO’s of Alternate Exchange companies are compensated 12% less than their JSE main board counter parts. Company performance is measured using both return on equity and annual percentage change share price while company size is measured by total assets and growth opportunities by Tobin’s Q. The listing boards are contrasted using fixed effect time series panel regressions of companies on each index separately and then with the entire sample of companies while measuring the effect of index in the form of a dummy variable. No significant relationship between CEO compensation and company performance was found for ALTX listed companies while for JSE main board listed companies, company performance measured using annual change in share price was positively associated with CEO compensation which indicates that agency problems could be prevalent at ALTX listed companies. The difference in the relationship between CEO compensation and company performance for JSE main board versus ALTX listed companies is attributed to governance regulations. The presence of a designated advisor therefore results in CEO’s receiving less compensation however comply or explain regulations requiring the presence of a remuneration committee, preventing CEO duality and board independence is associated with a stronger relationship between company performance and CEO compensation. The paper therefore highlights whether lower CEO compensation absolutely is preferable to CEO compensation that is better justified because of a dependence on company performance and how this consideration relates to a company being listed on either the JSE main board or the ALTX.
Keywords: Johannesburg Stock Exchange.Executives -- Salaries, etc. -- South Africa. Corporate governance -- South Africa.